The Form of Ideology and the Ideology of Form - Orsini, Francesca,Srivastava, Neelam,Zecchini, Laetitia (Open Book Publishers, 2022)
This timely volume focuses on the period of decolonization and the Cold War as the backdrop to the emergence of new and diverse literary aesthetics that accompanied anti-imperialist commitments and Afro-Asian solidarity. Competing internationalist frameworks produced a flurry of writings that made Asian, African and other world literatures visible to each other for the first time. The book's essays examine a host of print culture formats (magazines, newspapers, manifestos, conference proceedings, ephemera, etc.) and modes of cultural mediation and transnational exchange that enabled the construction of a variously inflected Third-World culture which played a determining role throughout the Cold War.
Description based on publisher supplied metadata and other sources
Keywords: Transmission of texts–History–20th century; Electronic books